Molecular features determining different partitioning patterns of papain and bromelain in aqueous two-phase systems - Rocha, María Victoria (2013)
The partitioning patterns of papain (PAP) and bromelain (BR), two well-known cysteine-proteases, in polyethyleneglycol/sodium citrate aqueous two-phase systems (ATPSs) were determined. Polyethyleneglycols of different molecular weight (600, 1000, 2000, 4600 and 8000) were assayed. Thermodynamic characterization of partitioning process, spectroscopy measurements and computational calculations of protein surface properties were also carried out in order to explain their differential partitioning behavior. PAP was observed to be displaced to the salt-enriched phase in all the assayed systems with partition coefficients (KpPAP) values between 0.2 and 0.9, while BR exhibited a high affinity for the polymer phase in systems formed by PEGs of low molecular weight (600 and 1000) with partition coefficients (KpBR) values close to 3. KpBR values resulted higher than KpPAP in all the cases. This difference could be assigned neither to the charge nor to the size of the partitioned biomolecules since PAP and BR possess similar molecular weight (23,000) and isoelectric point (9.60). The presence of highly exposed tryptophans and positively charged residues (Lys, Arg and His) in BR molecule would be responsible for a charge transfer interaction between PEG and the protein and, therefore, the uneven distribution of BR in these systems.